Rational Drug Design for Pseudomonas aeruginosa PqsA Enzyme: An in silico Guided Study to Block Biofilm Formation - Shaker, Bilal; Ahmad, Sajjad; Thai, Thi Duc; Eyun, Seong-il; Na, Dokyun (Frontiers in Molecular Biosciences, 2020)
Pseudomonas aeruginosa is an opportunistic gram-negative bacterium implicated in acute and chronic nosocomial infections and a leading cause of patient mortality. Such infections occur owing to biofilm formation that confers multidrug resistance and enhanced pathogenesis to the bacterium. In this study, we used a rational drug design strategy to inhibit the quorum signaling system of P. aeruginosa by designing potent inhibitory lead molecules against anthranilate-CoA ligase enzyme encoded by the pqsA gene. This enzyme produces autoinducers for cell-to-cell communication, which result in biofilm formation, and thus plays a pivotal role in the virulence of P. aeruginosa. A library of potential drug molecules was prepared by performing ligand-based screening using an available set of enzyme inhibitors. Subsequently, structure-based virtual screening was performed to identify compounds showing the best binding conformation with the target enzyme and forming a stable complex. The two hit compounds interact with the binding site of the enzyme through multiple short-range hydrophilic and hydrophobic interactions. Molecular dynamic simulation and MM-PBSA/GBSA results to calculate the affinity and stability of the hit compounds with the PqsA enzyme further confirmed their strong interactions. The hit compounds might be useful in tackling the resistant phenotypes of this pathogen.